2020
DOI: 10.1016/j.csbj.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking COVID therapeutic targets: A structure-based rationale against SARS-CoV-2, SARS-CoV and MERS-CoV Spike

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 101 publications
(134 reference statements)
4
38
0
Order By: Relevance
“…All five of the favorable sites reported ( Fig 16 ) were also predicted within specific sequence regions identified by Trigueiro-Louro et al, as having favorable druggability properties [ 120 ]. The overlap of our results for S2 and the residues identified by Trigueiro-Louro et al, [ 120 ] are shown in ( Fig 17 ).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…All five of the favorable sites reported ( Fig 16 ) were also predicted within specific sequence regions identified by Trigueiro-Louro et al, as having favorable druggability properties [ 120 ]. The overlap of our results for S2 and the residues identified by Trigueiro-Louro et al, [ 120 ] are shown in ( Fig 17 ).…”
Section: Resultsmentioning
confidence: 73%
“…We present results for five favorable representative aromatic pharmacophore sites identified within the TOP50 S2 Spike segment ( Fig 16 ). The S2 segment also has been recently analyzed in detail Trigueiro-Louro et al, to identify segments that are attractive to target with regards to sequence/structure conservation between beta coronavirus strains as well as predicted druggability by residue [ 120 ]. All five of the favorable sites reported ( Fig 16 ) were also predicted within specific sequence regions identified by Trigueiro-Louro et al, as having favorable druggability properties [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations